Analysis of the high Reynolds number 2D tests on a wind turbine airfoil performed at two different wind tunnels. (September 2016) - Pires, O; Munduate, X; Ceyhan, O; Jacobs, M; Madsen, J; Schepers, J G
Abstract: 2D wind tunnel tests at high Reynolds numbers have been done within the EU FP7 AVATAR project (Advanced Aerodynamic Tools of lArge Rotors) on the DU00-W-212 airfoil and at two different test facilities: the DNW High Pressure Wind Tunnel in Gottingen (HDG) and the LM Wind Power in-house wind tunnel. Two conditions of Reynolds numbers have been performed in both tests: 3 and 6 million. The Mach number and turbulence intensity values are similar in both wind tunnels at the 3 million Reynolds number test, while they are significantly different at 6 million Reynolds number. The paper presents a comparison of the data obtained from the two wind tunnels, showing good repeatability at 3 million Reynolds number and differences at 6 million Reynolds number that are consistent with the different Mach number and turbulence intensity values.